2019
DOI: 10.1016/j.pmedr.2019.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gender and peer tobacco use on tobacco use intentions after a period of involuntary tobacco abstinence among U.S. Air Force trainees

Abstract: This study examined gender, prior tobacco use, and social-environmental factors as predictors of intentions to use tobacco (cigarette smoking and/or smokeless tobacco [ST]) after a forced period of abstinence among U.S. Air Force (USAF) trainees. Trainees completed 8½ weeks of basic military training (BMT), then 4 weeks of Technical Training; both required abstinence from tobacco. A cross-sectional survey of 13,514 USAF trainees (73% male, 90% age 18–24, 43% prior tobacco use) was conducted at the beginning of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
(68 reference statements)
1
3
0
Order By: Relevance
“…25 At the interpersonal level, our findings indicate that peers and superiors play a significant role in influencing smoking and quitting behaviours. Consistent with previous research, [26][27][28] peer influence was reported as a strong factor in developing normative perceptions regarding tobacco use in which smoking was perceived as a 'social activity' and 'social norm' in the military. Our participants perceived an unrealistic high smoking norms among peers, while in fact only about one in five were smokers in the SAF.…”
Section: Discussionsupporting
confidence: 85%
“…25 At the interpersonal level, our findings indicate that peers and superiors play a significant role in influencing smoking and quitting behaviours. Consistent with previous research, [26][27][28] peer influence was reported as a strong factor in developing normative perceptions regarding tobacco use in which smoking was perceived as a 'social activity' and 'social norm' in the military. Our participants perceived an unrealistic high smoking norms among peers, while in fact only about one in five were smokers in the SAF.…”
Section: Discussionsupporting
confidence: 85%
“…They are also consistent with a meta-analysis study by Leonardi-Bee et al 27 and systematic literature review by Kusel et al 18 , which found that the use of cigarettes significantly increased if at least one parent smoked, if mothers smoked, fathers smoked, both parents smoked, siblings smoked and other family members smoked. In another study, tobacco use was influenced by the number of close friends who smoked 28 .…”
Section: Discussionmentioning
confidence: 98%
“… 60 However, a ban on cigarettes resulted in the intention to start smoking twice more often in previously non-smoking women than men. 61 …”
Section: Discussionmentioning
confidence: 99%
“…60 However, a ban on cigarettes resulted in the intention to start smoking twice more often in previously non-smoking women than men. 61 The strength of this study is the use of focus groups, comparing women to men. This helps to develop a better understanding of gender differences in smoking cessation and thereby to better align interventions in primary care.…”
Section: Comparison With Literaturementioning
confidence: 99%